Legal Adaptation Of The Laws Regulating The Topics Referred To In Article (84/3) Of The Jordanian Constitution - Mohammad Ahmad Rahamneh (Journal of Legal Sciences, 2024)
The aim of the study was to determine the legal nature of the laws governing the topics referred to in Article (84/3) of the Jordanian constitution, as the legislator required any of the upper and lower houses of Parliament to issue a decision related to any of these laws with a strict majority that is somewhat similar to the majority required to approve the draft law amending the Constitution. Which called for a part of jurisprudence to consider these laws as complementary laws to the Constitution. The study came to demonstrate the validity of this hypothesis. In order to achieve the purpose of the study, the descriptive approach was used; by analyzing the relevant texts of the Constitution. The study has reached several conclusions, the most important of which is that the legal value of these laws does not differ from other laws, and the possibility of suspending their operation under defense orders issued based on the Defense (State of emergency) law. The study recommended that the interpretation of Article (84/3) of the Constitution should be requested to confront the mental image that surrounded these laws in the light of jurisprudence, by determining the legal nature of these laws and their value in the legislative pyramid in Jordan.